THE ASSOCIATION BETWEEN TELOMERE LENGTH, 21 NUTRIENTS AND A HEALTHY EATING INDEX IN THE NHANES 1999–2002. (11th November 2018) - Ghimire, S; Sy, F
Abstract: Introduction: Preservation of telomere length, a biomarker of aging, is hypothesized as one pathway by which proper nutrition can delay or prevent the development of chronic disease. The current study aims to comprehensively examine a large variety of nutrients for their potential to preserve telomere length. Additionally, the association between telomere length and healthy eating was examined. Methods: Cross-sectional data on 6645 non-pregnant individuals aged 20–84 years were included from National Health and Nutrition Examination Survey (NHANES) 1999–2002. Nutrients intake were energy-adjusted using the residual method to minimize measurement error in dietary estimates. Results: In a linear regression model, adjusted for demographics, health-related behaviors and an inflammatory biomarker, intakes of potassium (β= 0. 1104347, 95%CI: 0.0240812, 0.1967882), Vitamin B2 (β= 0. 0901791, 95%CI: 0.0053695, 0.1749888), Vitamin B6 (β= 0. 0724068, 95%CI: 0.0081196, 0.136694), total fat score (β= 0.0122125, 95%CI: 0.0028288, 0.0215962), and the overall healthy eating index score (β= 0.0040716, 95%CI: 0.0009278, 0.0072154) were positively associated with telomere length. In sensitivity analyses, compared to those who met the recommended dietary intake levels, individuals with less than the recommended intake of Vitamin B2 (β= -0.1141968, 95%CI: -0.2092438, -0.0191497) and Vitamin B6 (β= -0.0949459, 95%CI: -0.1699573, -0.0199345) had shorter telomeres. The findings were inconsistent in subgroup analysis by age, sex, chronic disease status, and use of dietary supplements. Conclusions: Our findings suggest that some nutrients in particular and healthy eating in general, easily achievable through nutritional supplementation and healthy diets, are associated with preservation of telomere length.